2019
DOI: 10.1101/542761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patterns of African and Asian admixture in the Afrikaner population of South Africa

Abstract: The Afrikaner population of South Africa are the descendants of European colonists who started to colonize the Cape of Good Hope in the 1600’s. In the early days of the colony, mixed unions between European males and non-European females gave rise to admixed children who later became incorporated into either the Afrikaner or the “Coloured” populations of South Africa. Ancestry, social class, culture, sex ratio and geographic structure affected admixture patterns and caused different ancestry and admixture patt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…On the other hand, the East African ancestry seems to be male-biased; with an X/A ratio of 0.42 ± 0.07 SD in the Hessequa descendants, 0.46 ± 0.09 SD in the Nama, 0.57 ± 0.13SD in the Khwe, 0.54 ± 0.23 SD in the ǂKhomani and 0.83 ± 0.23 SD in the Coloured population of Wellington. Similarly, we also see male-driven admixture for the European ancestry, as expected [ 55 ], with X/A averages ranging between 0.50 and 0.93.
Fig.
…”
Section: Resultssupporting
confidence: 84%
“…On the other hand, the East African ancestry seems to be male-biased; with an X/A ratio of 0.42 ± 0.07 SD in the Hessequa descendants, 0.46 ± 0.09 SD in the Nama, 0.57 ± 0.13SD in the Khwe, 0.54 ± 0.23 SD in the ǂKhomani and 0.83 ± 0.23 SD in the Coloured population of Wellington. Similarly, we also see male-driven admixture for the European ancestry, as expected [ 55 ], with X/A averages ranging between 0.50 and 0.93.
Fig.
…”
Section: Resultssupporting
confidence: 84%
“…The absence of CNVs in the White Afrikaner population with its European heritage is surprising, as many CNVs (including a founder variant reported for the Netherlands [62]) have been reported for this region of the world. Investigators genotyped a large subset (n = 7746) of Afrikaner individuals using ~5 million genome-wide markers to determine parental source populations worldwide [63]. The authors confirmed that ~95.3% of Afrikaner ancestry came from mostly northwestern European populations, with the remaining section contributed by admixture with slaves and the local Khoe-San groups [63].…”
Section: Discussionmentioning
confidence: 93%
“…Investigators genotyped a large subset (n = 7746) of Afrikaner individuals using ~5 million genome-wide markers to determine parental source populations worldwide [63]. The authors confirmed that ~95.3% of Afrikaner ancestry came from mostly northwestern European populations, with the remaining section contributed by admixture with slaves and the local Khoe-San groups [63].…”
Section: Discussionmentioning
confidence: 93%
“…19 Founder effects for a number of diseases have been observed in this population, possibly due to the fact that the disease alleles were present in the original progenitors and were later amplified through exponential population expansion. 20 However, it is important to note that the fact that a disease is more common in some populations than in others does not mean it is exclusive to a particular population. The same genetic diseases can be found across all populations in the world.…”
Section: Selective Advantagementioning
confidence: 99%